(untitled) (Research, Society and Development, 2020)
The study evaluated the effect of the application of simplified or full-step surface treatments and aging times on dentin bonding stability and nanoleakage of indirect resin composite restorations. This is an in vitro study with one hundred and sixty indirect resin composite restorations (4.8 x 2.8 x 4.0 mm) produced to fill dentin preparations in bovine dentin. The specimens were divided into eight groups according to chemical treatment [No treatment; Silane; Scotchbond™ Universal adhesive (SBU); and Silane + SBU], and aging time in water [24 h and six months]. Push-out bond strength (PBS) was evaluated by a universal testing machine (1.0 mm/min), failure modes by a dissecting microscope, and nanoleakage by scanning electron microscopy. Two-way ANOVA and Tukey posthoc tests (p<0.05) were used to compare PBS among the groups, while failure modes and nanoleakage were analyzed descriptively. The bonding stability of indirect resin composite restorations was influenced by chemical surface treatments and aging times (p <0.05). Significant differences were determined between chemical treatment applied, mainly when SBU was used after aging the samples. The different surface treatments and aging time did not influence the nanoleakage at the cement-resin interface. The study results suggest that the simplified surface treatment using a universal adhesive improved the dentin bonding stability of indirect resin composite restorations.